Urine-based antigen detection assay for diagnosis of visceral leishmaniasis using monoclonal antibodies specific for six protein biomarkers of Leishmania infantum / Leishmania donovani. - Claudia Abeijon; Fabiana Alves; Séverine Monnerat; Jane Mbui; Agostinho G Viana; Raquel M Almeida; Lilian L Bueno; Ricardo T Fujiwara; Antonio Campos-Neto (Public Library of Science (PLoS), 2020)
The development of an accurate protein-based antigen detection assay for diagnosis of active visceral leishmaniasis (VL) would represent a major clinical advance. VL is a serious and fatal disease caused by the parasites Leishmania infantum and Leishmania donovani. The gold standard confirmatory diagnostic test for VL is the demonstration of parasites or their DNA from aspirates from spleen, lymph node, and bone marrow or from blood buffy coats. Here we describe the production and use of monoclonal antibodies (mAbs) for the development of a sensitive and specific antigen detection capture ELISA for VL diagnosis. This test simultaneously detects six leishmania protein biomarkers that we have previously described (Li-isd1, Li-txn1, Li-ntf2, Ld-mao1, Ld-ppi1 and Ld-mad1). The initial clinical validation of this new mAb-based multiplexed capture ELISA showed a sensitivity of ≥93%. The test was negative with 35 urine samples from healthy control subjects as well as with 30 patients with confirmed non-VL tropical diseases (cutaneous leishmaniasis, n = 6; Chagas disease, n = 6; schistosomiasis, n = 6; and tuberculosis, n = 12). These results strongly support the possible utility of this mAb-based multiplexed capture ELISA as a promising diagnostic test for active VL as well as for monitoring the treatment efficacy of this disease. The test is ready for upscaling and validation for clinical use.